Interaction of pyrite with zerovalent iron with superior reductive ability via Fe(ii) regeneration. Issue 8 (24th June 2022) - Li, Qi; Jiang, Zhi; Zheng, Junhao; Xie, Yan; Liao, Qi; Zhao, Feiping; Yang, Zhihui; Lin, Zhang; Si, Mengying; Yang, Weichun
Abstract : Sulfidation of zero-valent iron (SZVI) emerged as a promising approach to enhance both the reactivity and selectivity of nano zero-valent iron (ZVI). Abstract : Sulfidation of zero-valent iron (SZVI) emerged as a promising approach to enhance both the reactivity and selectivity of nano zero-valent iron (ZVI). However, the dense base layer of the Fe 0 core–FeS x shell structure inhibited the Fe(ii ) regeneration and the applicable pH range was narrow (only acidic conditions), thus limiting the application of SZVI. In this work, a structure with a substrate of pyrite and well dispersed ZVI (FeS2 /ZVI) was developed. The interaction of pyrite with Fe 0 significantly promoted the generation of Fe 2+ . More than 99.9% of Cr(vi ) (50 mg L −1 ) was removed within 2 h, which was 3.7–8.9 times higher than that of the precursor alone. During Cr(vi ) removal, Fe 0 and FeS2 reacted with Fe 3+ to regenerate Fe 2+ and H +, promoting the Cr(vi ) reduction and extending the applicable pH range to 3.04–9.20. Moreover, the effects of S species (S2 2−, S 2−, and S 0 ) in sulfide precursors on the crystal structure, electron transfer capacity, and Fe(ii ) cycling ability of SZVI were further revealed. The introduced S2 2− promoted the formation of a galvanic couple between FeS2 (+0.35 V) and Fe 0 (−0.44 V), thus accelerating the electron transfer from ZVI and releasing more Fe(ii ) for Cr(vi ) reduction. This study developed an efficient approach for ZVI activation and contributed to the insight into the enhanced mechanism of incorporated sulfur.